1984
DOI: 10.1073/pnas.81.8.2332
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of cDNA for Avena phytochrome

Abstract: We have isolated several cDNA clones for phytochrome, a plant regulatory photoreceptor. A cDNA library was constructed by using etiolated Avena poly(A)+ RNA enriched for phytochrome mRNA by size fractionation. Replicate arrays of colonies were differentially screened with cDNA probes made from poly(A)+ RNA that had been either enriched in or depleted of phytochrome mRNA. Of the colonies hybridizing preferentially with the enriched probe, several contained plasmids that specifically selected phytochrome mRNA wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

1985
1985
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 41 publications
3
33
1
1
Order By: Relevance
“…The organ-and tissuespecific expression profiles of PHYB genes in tomato relative to white light in blade, sheath, and mesocotyl tissues. This light-dependent decrease in phyA tran- (Hauser et al 1997) and tobacco (Adam et al 1996) and maize (this study) contrast with the relatively uniform scripts has been observed in several grass species (Colbert et al 1983;Hershey et al 1984; Christensen and pattern of PHYB expression in Arabidopsis (Somers and Quail 1995b) and potato (Heyer and Gatz 1992) and Quail 1989;Kay et al 1989;Dehesh et al 1991) and likely reflects a common regulatory mechanism that acts suggest that there may be little conservation in the transcriptional regulation of PHYB and PHYC accumulation to maintain high levels of phyA transcript in the dark (Bruce et al 1989). Furthermore, several elements have between monocots and dicots.…”
Section: Bac Library Screenscontrasting
confidence: 45%
“…The organ-and tissuespecific expression profiles of PHYB genes in tomato relative to white light in blade, sheath, and mesocotyl tissues. This light-dependent decrease in phyA tran- (Hauser et al 1997) and tobacco (Adam et al 1996) and maize (this study) contrast with the relatively uniform scripts has been observed in several grass species (Colbert et al 1983;Hershey et al 1984; Christensen and pattern of PHYB expression in Arabidopsis (Somers and Quail 1995b) and potato (Heyer and Gatz 1992) and Quail 1989;Kay et al 1989;Dehesh et al 1991) and likely reflects a common regulatory mechanism that acts suggest that there may be little conservation in the transcriptional regulation of PHYB and PHYC accumulation to maintain high levels of phyA transcript in the dark (Bruce et al 1989). Furthermore, several elements have between monocots and dicots.…”
Section: Bac Library Screenscontrasting
confidence: 45%
“…Interestingly, the minimum PHYA tail length in poly(A)+ RNA (-24 nucleotides) was similar to the minimum size to which the poly(A) binding protein (PABP) will associate (Baker, 1993). Previously, the oat fulllength PHYA mRNA was estimated to be 4.2 kb in size (Hershey et al, 1984). However, from the RNase H poly(A) tail data and the known length of PHYA cDNA clones (Hershey et al, 1985), the size of the polyadenylated full-length PHYA mRNA is calculated to be 4030 nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…An Avena sativa cDNA library with G+C-tailed inserts harbored in pBR322 was generously provided by J. Lissemore and P. Quail (13 Approximately 100,000 plaques of an A. thaliana cDNA phage library were screened with a 0.6-kb fragment that was gel-purified from the oat clone pTS.6. Two independent clones, pAHA1-11 and pAHA2, were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The plasma membrane proton pump has only been observed in plants and fungi and was characterized by biochemical and electrophysiological techniques (1,8 An Avena sativa cDNA library with G+C-tailed inserts harbored in pBR322 was generously provided by J. Lissemore and P. Quail (13). Colony hybridizations were performed at 30°C in 6x SSC (lx = 0.15 M NaCl/0.015 M sodium citrate, pH 7.0)/i x Denhardt's solution (lx = 0.02% polyvinylpyrrolidone/0.02% Ficoll/0.02% bovine serum albumin)/0.05% (wt/vol) sodium pyrophosphate/yeast tRNA at 100 ,ug/ml/20% (vol/vol) formamide containing 1.1-2.2 x 107 dpm of 32P-labeled GDGV26I per ml.…”
Section: Introductionmentioning
confidence: 99%